Risk factors for cardiovascular disease in the Chinese population: recent progress and implications - Yuanjie Pang; Jun Lyu; Canqing Yu; Yu Guo; Liming Lee (Global Health Journal, 2020)
Cardiovascular disease (CVD) is the leading cause of death in both urban and rural areas of China. The current evidence regarding CVD risk factors was primarily established in Western countries, with limited generalizability to the Chinese population. In China, a growing number of population-based prospective cohort studies have emerged that have yielded substantial research data on CVD risk factors in the past five years. The research studies have covered biological risk factors (e.g., blood lipids, blood pressure, blood glucose, adiposity), lifestyle risk factors (e.g., smoking, alcohol, diet, physical activity), environmental risk factors (e.g., ambient and indoor air pollution), and risk prediction. This study aimed to systematically review the research progress on CVD risk factors in the Chinese population in the past five years. Prospective studies in China have identified biological, lifestyle, and environmental risk factors for CVD and its main subtypes, along with some protective factors unique to the Chinese (e.g., spicy food and green tea). This review aimed to provide high-quality evidence for achieving the Outline of Healthy China 2030, developing disease prevention guidelines and measures, and deepening efforts for popularization of health knowledge.